Documentation of food handling practices in relation to health conditions of children aging 0 to 6 years old in Barangay Lanag Sur, Tubungan, Iloilo. - Arcolas, Kezia Lois; Belleza, Noel Francis; De Leon, Mary Antonette
Improper home food handling preparation and consumption practices by consumers, inadequate hygiene practices, consumption of raw and unsafe food, as well as cross contamination by raw food are some factors and practices that have been implicated in food borne outbreaks in the home (Taulo et. al., 2006). A survey was conducted to 27 households with children aged 0-6 years old from Barangay Lanag Sur, Tubungan, Iloilo. Of the 27 respondents, majority belong to the 30-39(46.15 percent) age group, are housewives(65.38 percent) who were also in charge in preparing the food(53.8 percent), with monthly income ranging from 0-4999 pesos(57.69 percent). Among the respondents, six of them were randomly taken for sources of food sample which was tested for physical and microbial examination. Based on the survey food preparation practices of households in the barangay is composed of washing, cutting, rewashing, boiling to cook/sterilize (for infant formulas), and cooling to room temperature. Majority of the respondents consume right kind of food essential for nutritional use and use untreated spring water for its preparation. Food samples taken have pH values ranging from 6.15 to 6.975. The test for coliform indicated that two out of six households were positive for presence of coliform. Among the common illnesses of children recorded, 96 percent have had a history of acute respiratory infections and 84 percent have had episodes of gastrointestinal illness. Food handling practice in the community is simple and not capable of eliminating pathogenic subtances like coliform bacteria totally.